Radiological impact assessment of nuclear weapon depots in Valley Rwagh, Libya - Elnimr, M. A.; Turhan, Ş.; Khalid, M. M.; Ali Madee, Y. G.; Gala, H.; Kurnaz, A.; Hançerlioğulları, A. (Informa UK Limited, 2017)
ABSTRACTActivity levels of the natural (238U, 232Th, 226Ra, and 40K) and artificial (137Cs) radionuclides in surface soil samples collected from different areas of Libya, especially the southern and central provinces, including Valley Rwagh, which is in a mountainous region in Al-Jufra Oasis amid the Libyan desert, 600 km southeast of Tripoli, and in which there are stores of various weapons, were determined using a gamma-ray spectrometer with a HPGe detector. The average activity concentrations of 238U, 232Th, 226Ra, and 40K were measured as 87 ± 11, 202 ± 36, 121 ± 19, and 73 ± 3 Bq kg–1, respectively. The activity levels of artificial radionuclide 137Cs measured in soil samples were below the detection limit. The average concentrations of radon in soil and air were estimated as 103 kBq m–3 and 327 Bq m–3, respectively. The average values of outdoor absorbed gamma dose rate and the corresponding annual effective dose rate from external exposure, annual effective dose rate from inhalation of radon, and l...
Keywords: 13. Climate action